Robinson Crusoe after 300 years - Mueller, Andreas Karl Ewald, 1972-; Ridley, Glynis (Transits (Bucknell University), 2021)
"When Defoe published The Life and Strange Surprizing Adventures of Robinson Crusoe and The Farther Adventures of Robinson Crusoe in 1719, he could not have imagined that Crusoe, Friday, and a footprint in the sand would enjoy global recognition 300 years later. Why-and how-does Crusoe's story resonate today? There is no shortage of explanations for the longevity of Defoe's creation, which has been interpreted as both religious allegory and frontier myth, with Crusoe seen as an example of the self-sufficient adventurer and the archetypal colonizer and capitalist. Defoe's original has been reimagined multiple times in legions of Robinsonade or castaway stories. But there is still much more to say-the Crusoe myth is far from spent. This wide-ranging collection brings together eleven scholars who suggest new and unfamiliar ways of thinking about this most familiar of works, and who ask us to consider the enduring appeal of "Crusoe," more recognizable today than ever before"--